The Effect of Audit Committee, Company Size, Independent Board of Commissioners, And Solvency on Audit Delay in Property and Real Estate Sub-Sector Companies Listed on The IDX In 2021-2023 - Tiorika Nababan; Angel Angel; Evelyn Evelyn; Jennifer Cu; Siswanto Siswanto (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2026)
This study was conducted to investigate the influence of audit committee, company size, independent board of commissioners, and solvency on audit delays in property and real estate sub-sector companies listed on the Indonesia Stock Exchange in the 2021–2023 period. Timeliness in the submission of audited financial statements is a crucial factor in maintaining the relevance and credibility of financial information for stakeholders, so audit delays are an important indicator to be studied. The approach used in this study is quantitative by utilizing secondary data sourced from the company's annual financial statements. The number of samples analyzed was 171 observations obtained through purposive sampling techniques. Hypothesis testing was carried out using multiple linear regression analysis. The study's findings show that audit committees, company size, and independent board of commissioners do not show a significant influence on audit delays. Conversely, solvency has been shown to have a positive and significant influence, meaning that an increase in solvency is likely to be followed by an increasing length of audit completion process, along with increasing complexity of funding structures and audit risks that must be examined in more depth. Simultaneously, all independent variables have a significant influence on audit delays. The results of this study are expected to enrich the literature related to the timeliness of audits and provide insight for management and stakeholders in understanding the factors that affect audit delays.